Wolfgang Berkowski : Incidental Arrangements. (Paris : Onestar Press Paris, 2001)
Inccidental Arrangements displays some of the main strategies used by the artist. The three parts (Connectors, Milieu and Cover) each form a distinct project, utilizing acquisition and choice, abstraction and memory, the real world and the laboratory as point of view, while taking up links to each other, like dendrites creating a network between different regions of a brain. As a result this book resembles a manual of how to's rather than a fixed entity.
Along with "Incidental Arrangements" a second book: "Arranged incidents" is published in association with Onestar Press
biog. [1 p.]
Engels
boek
Keywords: Berkowski, Wolfgang